ANALISIS KEMAMPUAN KEUANGAN DAERAH DALAM PELAKSANAAN OTONOMI DAERAH (STUDI KASUS KOTA PEKANBARU PERIODE 2005-2014) - Rini Maidra Putri; Gusnardi '; RM Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : the research aims to detemine finance capacity of Pekanbaru in the implementasion of regional autonomy among 2005-2013. This study is a descriptive comparative study with the object of study is Pekanbaru city Central Bureau of Statistics. Secondary data is needed is the realization of the reflected toward budget revenue and expenditure in 2005 – 2014. Methodology of data collection used in this study documentation. Analysis of the data used: 1. The independence ratio of the financial area, 2. The autonomy ratio of the fiscal degree, 3. The index of ratio routin capability, 4. The accord of ratio, 5. The growth of ratio. The result showed: 1. The independence ratio of the financial area is insturctive pattern, 2. The degree of fiscal decentralization are at less intervals that is 17,06%. 3. Ratio routine capability index is less scale that is 23,24%. 4. The accord of ratio showed the result of routine expenditure is greater than the development expenditure amounted to 68,09% and 29,89% of development expenditure. 5. Finally, the growth occured in positive growth. Keywords : Regional Autonomy, The Capacity Of Local Financial